Cd and Nutrient Elements Release into Various Aqueous Solutions from Synthesized K-Struvite Fertilizer - Arslanoglu, Hasan; Tumen, Fikret (Taylor & Francis Inc, 2018)
K-struvite (potassium magnesium phosphate, KMgPO4.6H(2)O) is a promising multinutrient slow-release fertilizer; however, it may contain cadmium (Cd) in significant ranges like other phosphorus (P) fertilizers. This paper focuses on dissolution of a synthesized K-struvite in water, acid solutions and complexing agents. Firstly, K-struvite was synthesized by using Cd containing phosphoric acid (H3PO4). After its characterization, a three-stage dissolution study was carried out. The release of nutrient elements and Cd into extracts was studied. Phosphorus (P) and potassium (K) solubilities in pure water are low, not more than about 2.5% at the end of three extractions. It was found that solubility increased with the presence of mineral and organic acids. The presence of complexing agents also enhanced the dissolution of K-struvite. At the end of three extractions, citric acid (CA, C6H8O7.H2O) solution solubilized P about 38%, while dissolved K was about 35%, in cumulative. In the case of 0.001mol/L Na(2)EDTA (C10H14N2Na2O8.2H(2)O), the solubilized K-struvite was found to be about 40%, which was about 14% in a 250mg/L Na-humate. The maximum concentrations of Cdin the third extracts of hydrochloric acid (HCl), CA, oxalic acid (OA, C2H2O4) and Na(2)EDTA were measured to be in the range of about 14-19 g/L, which corresponds to a Cd solubilization more than 46% for the three successive extractions.
Keywords: Cadmium; dissolution; fertilizer; K-struvite; slow-released